2015
DOI: 10.1364/oe.23.009483
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic flowmeter based on micro “hot-wire” sandwiched Fabry-Perot interferometer

Abstract: We present a compact microfluidic flowmeter based on Fabry-Perot interferometer (FPI). The FPI was composed by a pair of fiber Bragg grating reflectors and a micro Co(2+)-doped optical fiber cavity, acting as a "hot-wire" sensor. Microfluidic channels made from commercial silica capillaries were integrated with the FPIs on a chip to realize flow-rate sensing system. By utilizing a tunable pump laser with wavelength of 1480 nm, the proposed flowmeter was experimentally demonstrated. The flow rate of the liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…1(b). It can be observed that even though at different fluidic conditions, the temperature increase follows a reasonable linear relationship with respect to the pumping power, which is similar to the heating process of hot fibers 2,8,14 . On the same amount of pumping power, the temperature difference between the flow sensor and oil is larger than water because the heat capacity of the former fluid is ~1.88 J .…”
Section: Introductionmentioning
confidence: 59%
“…1(b). It can be observed that even though at different fluidic conditions, the temperature increase follows a reasonable linear relationship with respect to the pumping power, which is similar to the heating process of hot fibers 2,8,14 . On the same amount of pumping power, the temperature difference between the flow sensor and oil is larger than water because the heat capacity of the former fluid is ~1.88 J .…”
Section: Introductionmentioning
confidence: 59%
“…The sensor is easy to fabricate with a simple and reliable structure. Besides, it shows an ultra-high sensitivity, which is almost one order of magnitude higher than previous reports when the flow rate is 1 μl/s [7,8]. The minimum detectable change of the flow rate is 9 nl/s at v 1 μl∕s.…”
mentioning
confidence: 61%
“…While at v 1 μl∕s, the sensitivities are approximately 1.092, 1.637, and 2.183 nm/(μl/s), when the incident power is also set to 100, 150, and 197 mW. At v 1 μl∕s, there is almost one order of magnitude improvement in the sensitivity than for previous reports [7,8]. Because the resolution of the OSA is 0.02 nm, the minimum detectable change of the flow rate is approximately 48 nl/s at v 3 μl∕s and 9 nl/s at v 1 μl∕s when the incident power is 197 mW.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Such effects can also be recognized by the DNN to measure the concentration. There are alternative methods for measuring the flow rate [14][15][16][17] or the dilution ratio [18][19][20][21] in a microfluidic chip. The two prominent methods for on-chip flow measurements are the Coriolis method 17 , based on mechanical oscillations that depend on the flow rate, and thermal measurement 16 , in which a heater and thermometer are used to measure temperature changes in the flow.…”
mentioning
confidence: 99%